Geochemistry, Geochronology, and Hf isotopic Composition of the Late Paleoproterozoic Lujiapuzi Formation, NE Yan‐Liao Rift, Northern Liaoning. (27th December 2018) - LIU, Jin; ZHANG, Jian; LIU, Zhenghong; YIN, Changqing; ZHAO, Chen; PENG, Youbo; DOU, Shiyong; YANG, Zhongjie
Abstract : Abstract : The metasedimentary Lujiapuzi Formation crops out along the northeastern margin of the North China Craton, close to the Yan‐Liao Rift. The age and tectonic setting of the formation, and its relationship with the Yan‐Liao Rift are currently unclear. Here we present detrital zircon U‐Pb ages, and Hf isotopic and geochemical data for the Lujiapuzi Formation to constrain the timing of deposition, the provenance of the formation, and the regional stratigraphy relationship. Zircon U‐Pb dating constrains the timing of deposition of the Lujiapuzi Formation to younger than 1780 Ma, and indicates that most grains were sourced from the Longgang Block and the Paleoproterozoic Liao‐Ji Belt. Detailed field investigations and a correlation of the regional stratigraphy reveal that much of the Lujiapuzi Formation is equivalent to the Tuanshanzi Formation in the Yan‐Liao Rift; the lower section may represent the earliest sediments deposited within the Fanhe Basin. Based on these results and the findings of previous studies, we suggest that the base of the Changcheng System has an age of 1.80 Ga. Zircon Hf isotopic data indicate that the main period of crustal growth along the northeastern margin of the North China Craton occurred at 3.2–2.5 Ga, with a peak at 2.9–2.7 Ga.